PELAYANAN PUBLIK PAJAK KENDARAAN BERMOTOR OLEH BADAN PENDAPATAN DAERAH PROVINSI RIAU (Studi Kasus Unit Pelaksana Teknis Pendapatan Rokan Hilir Tahun 2015-2017) - Idriansyah, Muhammmad Ficri; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Motor Vehicle Tax (PKB) is a tax on motorized vehicles with tax objects, as stated in the Regional Regulation of Riau Province Number 4 of 2015, covering ownership and / or control of motorized vehicles. Establishment of Technical Implementation Unit (UPT) Revenue from Rokan Hilir Bapenda in Riau Province aims to further intensify PKB through collecting PKB in the area of Rokan Hilir Regency in achieving the realization of the PKB target. However, in the PKB service to achieve the realization of the PKB target the lack of socialization in raising awareness of taxpayers, both regarding the usefulness of taxes, and sanctions on tax arrears so that the value of the PKB fine is Rp. 483,636,766 in that year 2017. The formulation and purpose of the research problem is to find out the public service of motor vehicle tax by UPT Rokan Hilir Revenue and the factors that influence PKB services by Revenue UPT of Rokan Hilir Regency in 2015-2017. The research method used is descriptive qualitative method with data collection instruments including interviews, documentation studies related to research objectives. The results of the study illustrate that the public service of motor vehicle tax by the Revenue Agency of Riau Province Rokan Hilir Revenue in 2015-2017 PKB public service at UPT Revenue Rokan Hilir focused more on public accountability, namely the existence of clear legislation (Perda and Pergub Riau Province ) as a line of policy, and the existence of rules for mechanisms, and clear service channels. However, the Revenue Unit of Rokan Hilir has not been able to respond to satisfaction of taxpayers with the unavailability of information counters and complaint handling, suggestion / criticism boxes in order to assess service performance. The service orientation is only focused on administrative services at the Rokan Hilir Revenue Unit UPT office. In addition, service efficiency, in the form of inputs (HR and Prasana Service Facilities) in carrying out operational duties and functions is inadequate which results in a decrease in the PKB target and the high delinquency of PKB in 2015-2017 or lack of taxpayers in paying PKB.Keywords: Taxes, Public Services, Service Accountability